On Characterizing Generalized Cambanis Family of Bivariate Distributions (Global Journal of Science Frontier Research, 2017)
In this work we present characterizations of a generalized version of Cambanis family of bivariate distributions. This family contains extensions of the Farlie-Gumbel-Morgenstern system as special cases. The characterizations are by properties of P(X>Y), regression functions and E(XjX > Y) which were found to be useful in many applications.
Keywords: cambanis family; FGM system; characterization; regression functions; conditional expectations